Dectin-1 is a major beta-glucan receptor on macrophages. - Brown, G; Taylor, P; Reid, D; Willment, J; Williams, D; Martinez-Pomares, L; Wong, S; Gordon, S (2002)
Zymosan is a beta-glucan- and mannan-rich particle that is widely used as a cellular activator for examining the numerous responses effected by phagocytes. The macrophage mannose receptor (MR) and complement receptor 3 (CR3) have historically been considered the major macrophage lectins involved in the nonopsonic recognition of these yeast-derived particles. Using specific carbohydrate inhibitors, we show that a beta-glucan receptor, but not the MR, is a predominant receptor involved in this process. Furthermore, nonopsonic zymosan binding was unaffected by genetic CD11b deficiency or a blocking monoclonal antibody (mAb) against CR3, demonstrating that CR3 was not the beta-glucan receptor mediating this activity. To address the role of the recently described beta-glucan receptor, Dectin-1, we generated a novel anti-Dectin-1 mAb, 2A11. Using this mAb, we show here that Dectin-1 was almost exclusively responsible for the beta-glucan-dependent, nonopsonic recognition of zymosan by primary macro-phages. These findings define Dectin-1 as the leukocyte beta-glucan receptor, first described over 50 years ago, and resolves the long-standing controversy regarding the identity of this important molecule. Furthermore, these results identify Dectin-1 as a new target for examining the immunomodulatory properties of beta-glucans for therapeutic drug design.